Reasoning about obligations in Obligationes: a formal approach - Uckelman, Sara L. (Advances in modal logic, volume 10, 2014)
Despite the appearance of ‘obligation’ in their name, medieval obligational disputations between an Opponent and a Respondent seem to many to be unrelated to deontic logic. However, given that some of the example disputations found in medieval texts involve Respondent reasoning about his obligations within the context of the disputation, it is clear that some sort of deontic reasoning is involved. In this paper, we explain how the reasoning diﬀers from that in ordinary basic deontic logic, and deﬁne dynamic epistemic semantics within which the medieval obligations can be expressed and the examples evaluated. Obligations in this framework are historybased and closely connected to action, thus allowing for comparisons with, e.g., the knowledge-based obligations of Pacuit, Parikh, and Cogan, and stit-theory. The contributions of this paper are twofold: The introduction of a new type of obligation into the deontic logic family, and an explanation of the precise deontic concepts involved in obligationes.